Counting of Z-generation with the development of work-based characters in practices learning - Hera Yuliana (Universitas Sarjanawiyata Tamansiswa, 2018)
The purpose of this research and development is to describe the implementation of industry-based work character development in practical learning that can equip students as Z-generation and to define the feasibility level of industry-based work character-based practice learning methods that can improve student learning achievement as Z-generation. Used in this study is the method of research and development (R & D). The development procedure uses the Borg and Gall models. The data subjects were class XI ATPH students in 2 classes as a control and experimental group — data collection techniques with learning observation, validation questionnaire, and documentation. While data analysis uses qualitative and quantitative descriptive analysis, the results of the study produced a guidebook, learning tools, and assessment tools. Evaluation of products and learning devices is feasible and can be used for trials. While the effectiveness of the product developed can improve student learning achievement.